Serviço social e saúde coletiva: apropriações e ardis no debate sobre as classificações internacionais em saúde - Alcantara, Ariana Celis (2022)
This thesis aims to present and discuss the debate on international health classifications and their appropriation by the Social Work. The International Health Classification Family, organized by the World Health Organization (WHO), is composed of the International Statistical Classification of Diseases and Related Health Problems (ICD), the International Classification of Functioning, Disability and Health (ICF) and the International Health Interventions (ICHI). An analysis, which permeates research of such studies, was conducted through systematic searches of qualitative studies, with a focus on studies that select this work. We conclude that appropriation, with in-depth studies and Social Work of the CIF and the CID, is a path that must be followed by the social. The study of movement that the classifications are producers of epidemiological data, has the power to move calculated figures and are disputed by the capitalist system. The dispute is not just about the classifications themselves and their meanings but permeates the movement to co-opt the WHO governance itself. With the use of consultations for the technical record of the social worker, the use of the ICF as a basis for the IF-M is highlighted and defends as an instrument for the biopsychosocial assessment of disability, the use of the ICD-11, on the other hand, needs further biopsy studies and evaluation